Microbial Inhibition by UV Radiation Combined with Nisin and Shelf-Life Extension of Tangerine Juice during Refrigerated Storage - Isaya Kijpatanasilp; Khursheed Ahmad Shiekh; Saeid Jafari; Randy W. Worobo; Kitipong Assatarakul (Foods, 2023)
This study evaluated the efficiency of UV radiation doses (4.68–149.76 J/cm2) and nisin (50–200 ppm) and their combination in comparison with thermal pasteurization on the microbial inhibition kinetics and physicochemical properties of tangerine juice. It was noted that UV-149.76 J/cm2 and nisin (NS) at 200 ppm in conjunction exhibited the highest log reduction in spoilage and pathogenic microbes including Escherichia coli, Lactiplantibacillus plantarum, and Saccharomyces cerevisiae, yeast and molds, and total plate count in tangerine juice. Additionally, the first-order kinetic model provides a better fit for spoilage and pathogenic strains compared with the zero-order model (higher coefficient of determination, R2), particularly for E. coli. UV and NS showed insignificant effects (p > 0.05) on pH, TSS, and TA values compared with pasteurization. However, there were notable differences observed in color analysis, total phenolic compound, total flavonoid content, vitamin C, carotenoid content, and antioxidant activity using DPPH and FRAP assays. The optimized UV + NS samples were subjected to refrigerated storage for 21 days. The results revealed that during the entire storage period, the pH values and the TSS values slightly decreased, and the TA values increased in the treated samples. The UV + NS treatment insignificantly impacted the color properties. The total phenolic, total flavonoid, and carotenoid contents, and vitamin C decreased over time for all sample treatments, whereas the antioxidant properties exhibited varying outcomes, compared with an untreated control and pasteurization. Therefore, UV radiation and nisin (UV-149.76 J/cm2 + NS-200 ppm) in combination could serve as a viable alternative to traditional heat pasteurization of fruit juice during cold storage.